Development of Oil Drops Practicum Guide Possession with Liquid Glycerol as Source of Oil Granules - Adinda Kurnia Komalasari; Sri Purwaningsih; Neneng Lestari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to develop a printed practicum guide for the Millikan oil drop experiment using glycerol liquid as a source of oil droplets and to determine its feasibility based on expert validation and student perceptions. The study employed a Research and Development (R&D) approach using the 4-D development model proposed by Thiagarajan, consisting of the define, design, develop, and disseminate stages. The research was conducted with 35 Physics Education students of the Faculty of Teacher Training and Education, University of Jambi, who were enrolled in the Physics Experiment course. Data were collected through observation, interviews, validation questionnaires, and student response questionnaires. The developed practicum guide was evaluated by material and media experts using a four-point Likert scale. The material validation results showed an average score of 3.8 with a feasibility percentage of 95%, indicating a very good category. The media validation results obtained an average score of 3.5 with a feasibility percentage of 88.3%, also categorized as very good. Furthermore, student perception data showed an average score of 3.51 with a percentage of 87.96%, indicating that the practicum guide was highly accepted and considered useful for supporting independent learning. These findings demonstrate that the developed practicum guide is valid, practical, and feasible to be used as a learning resource in physics experiment courses, particularly for the Millikan oil drop experiment using glycerol liquid.